Effects of radiotransmitters and breeding effort on harvest and survival rates of female mallards - Todd W. Arnold; David W. Howerter (Wildlife Society Bulletin)
Abstract There has been widespread speculation that breeding activity places adult female mallards (Anas platyrhynchos) at heightened risk of harvest due to insufficient time to complete the wing molt or recover body condition prior to onset of hunting and autumn migration. We tested the hypotheses that breeding females have higher rates of harvest and reduced prospects for survival by estimating band recovery rates (f) and annual survival (S) in relation to individual measures of breeding effort for 3,055 adult female mallards that had been banded and radiomarked during the breeding season in the Prairie‐Parkland Region of Canada, 1993–2000. Birds that had been marked with external prong‐and‐suture transmitters had lower estimated survival rates (S = 0.518, SE = 0.118) than birds marked with implant transmitters (S = 0.731, SE = 0.061), but rates for birds marked with implant transmitters did not differ from expectations based on other studies for females marked only with legbands. After excluding external transmitters, we found that recovery rates were unaffected by any measures of reproductive effort, but annual survival was lower for females that tended broods to 60 days of age (S = 0.474 ± 0.115) versus females that never hatched a nest (S = 0.654 ± 0.042). Telemetry data indicated that brood‐rearing females experienced extremely low mortality, so reduced survival of females that raised broods presumably resulted from insufficient time to molt and prepare for autumn migration. Management efforts that promote successful early nesting attempts may also improve adult female survival by allowing females more time to molt and prepare for autumn migration, whereas hunting regulations designed to protect late‐breeding females may prove ineffective if such individuals have higher natural mortality. © 2012 The Wildlife Society.